Inovações metodológicas em hematologia clínica: uso da citometria de fluxo no estudo da ativação plaquetária na pré-eclâmpsia - Leticia Goncalves Freitas (2012)
Preeclampsia (PE) is a serious complication of pregnancy associated to maternal-fetal morbidity and mortality, whose etiology has not been established. In pure form, is characterized by the appearance, in normal pregnant women after the 20th week of gestation, hypertension and proteinuria. Hemostatic and inflammatory changes associated with normal pregnancy are more exacerbated in PE. Studies suggest a marked platelet activation and aggregation contributing to the hypercoagulable state in this disease. Flow cytometry has been used to evaluate the expression of platelet surface glycoproteins, as well as the formation of platelet-leukocyte aggregates and the expression of tissue factor (TF) by monocytes. The aim of this study was to standardize techniques to evaluate the expression of platelet activation markers and expression of FT and apply them in the study of PE. We evaluated 97 women, of whom 35 were pregnant women with PE (15 with severe form-PEG and 20 with the mild form-PEL), 31 normotensive pregnant women (GN) and 31 nonpregnant women (CNG). Were evaluated mean fluorescence intensity (MFI) of the biomarkers CD41a, CD61, CD42a, CD62P and the ratio between them, and the percentage of platelets CD62P+, platelets-monocyte aggregates (APM), platelets-neutrophils aggregates (APN) and FT+ monocytes. The MFI of CD62P and the percentage of CD62P+ platelets in the three groups did not differ (p=0.67 and p=0.38, respectively). After the subdivision of the group of women with PE it was not obtained difference (p=0.69 for the IMF and p=0.54 for CD62P and CD62P+ platelets). The MFI of CD41a in pregnant women with PE were lower than in the CNG (p=0.004) compared to GN and CNG (p=0.007). The MFI of CD61 on the PEG group was lower than the CNG (p=0.008). The MFI of CD41a and CD61 was lower in the PE group than in the CNG and the GN in relation to the CNG (p=0.00 for both). Both were below the PEG and PEL in relation to the CNG (p=0.00 for both). The MFI of CD42a even after the subdivision of the PE group did not differ (p=0.44 and p=0.57, respectively). The rations between the MFI CD61/CD42a and CD41a/CD62P was lower in GN than in the CNG (p=0.002 and 0.007, respectively) and in the PE group compared to PEG and CNG (p=0.001 for both). The ratio MFI CD42a/CD41a was higher in the PE group compared to PEG and CNG (p=0.001 for both) and in relation to the CNG and GN (p=0.002). The reasons for the IMF CD61/CD41a, CD61/CD62P and CD42a/CD62P before (p=0.29; p=0.07 and p=0.73, respectively) and after (p=0.42; p=0.14 and p=0.69, respectively) the subdivision of the PE group did not differ. The percentage of APM before (p=0.08) and after division of the PE group (p=0.13) did not differ. The percentage of APN was lower PE in relation to CNG (p=0.01). There was no difference in the formation of APN in pregnant women with PE compared to GN (p=0.40) and between GN and CNG (p=0.018). There was no difference between groups after the subdivision of the PE group (p=0.02). The percentage of TF+ monocytes did not differ between groups before (p=0.14) and after the subdivision of the PE group (p=0.26). The study allowed the development of methodological innovations in Clinical Hematology to assess platelet activation. The standardization of the technique by flow cytometry to assess platelet activation and formation of APM and APN was established. Pregnancy is accompanied by changes in the expression of CD41a and CD61 on the platelet surface, and reduced platelet count. PE is accompanied by a lower percentage of APN in relation to CNG. The PEG is associated with a greater number of correlations between biomarkers of platelet activation suggesting that the process is multifactorial.